A facile microwave-assisted “one-pot” synthesis of piperazino pyrimidinyl acetamides, a class of hybrid bis heterocycles and their structural elucidation Using NMR spectral techniques - Ang, How Ghee (2013)
An array of novel piperazino pyrimidinyl acetamides, a class of hybrid bis heterocycles are synthesized in “one-pot” by microwave irradiation method catalyzed by heterogeneous NaHSO4.SiO2 catalyst in dry media and are characterized by melting point, elemental analysis, MS, FT-IR, one-dimensional NMR (1H and 13C) and two-dimensional 1H-1H COSY and 1H-13C HSQC spectral data.